Application of IoT Technology in Designing and Building an Automatic Plant Watering System Using Graph Chart and Blynk NodeMCU ESP8266 - Sapta, Lerry Salasi; Sumantri, Erno (Journal Innovations Computer Science, 2025)
This research developed an Internet of Things (IoT)–based automatic watering system designed to support the maintenance of Aglaonema ornamental plants. The system utilizes a NodeMCU ESP8266 microcontroller connected to a soil-moisture sensor and a DHT11 temperature sensor, all integrated with the Blynk mobile platform for real-time monitoring and remote control. By combining sensor feedback with automated logic, the system activates irrigation when soil moisture falls below 40 percent and stops it when levels exceed 60 percent. Laboratory and field testing confirmed that the prototype operated reliably within a six-meter Wi-Fi range, maintaining stable communication and accurate sensor readings. The device reduced water consumption by about 37 percent compared with manual watering and provided timely notifications through both the LCD display and the Blynk application. Although system performance depends on Wi-Fi connectivity and lacks backup power, its overall operation demonstrates that IoT-based automation can significantly improve water efficiency and convenience for small-scale plant owners. Future enhancement may include solar-powered modules, additional sensors, and cloud data storage to strengthen system reliability and expand smart-agriculture applications.